Pengolahan Limbah Cair Laboratorium Menggunakan Teknik Fotokatalisis Dengan TiO2 - adawiah, adawiah; Hanif, Muhammad Rusydi; Setiawan, Chepi; Alfatan, Alfi; Apriliani, Rika (UNISTEK, 2021)
Currently, the university is one of the actors in the use of chemical substances for educational purposes in practicums and research. Based on the survey, it is known that the processing of laboratory waste, especially organic wastewater, is not optimal. This needs to be considered considering that generally the university is located in the residential area so that if the wastewater pollutant, it will certainly risk causing serious impacts on the community. A wastewater treatment technology using photocatalysis can process toxic organic substances into simpler and environmentally friendly substances. This research includes several stages, namely the collection of waste organic compound from practicum and research activities, sampling of laboratory waste, and testing of waste treatment and analysis of the total content of organic compounds from permangnometric titration wastewater treatments. The results showed that the TiO2 photocatalyst with a composition of 0.8% (w / v) was able to reduce the content of organic compounds in the waste sample by 96.19027% in the reaction time of 4 days.